Metaliterature in Central America: "Cuaderno de Tokio", by Horacio Castellanos Moya - Montero Corrales, Cristopher (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
This article it's dedicated to the study of the metaliterary phenomenon in Central America during the XXI century, from the book Cuaderno de Tokio (2015), written by Horacio Castellanos-Moya. This narrative book constitutes a literature proposal where it explores the processes and problematics of "I", an I established as a writer-character, who reflects and gives testimony of the problems and processes of the creation and literary field. This allows us to inquire not only on the metaliterary core themes proposed by José A. Pérez Bowi but also inquire in the notions of a writer and literature that established this phenomenon in Central America.  Key wordsCentral American literature, salvadoran literature, metaliterature, Horacio Castellanos Moya, Cuaderno de Tokio
Keywords: Central american literature; salvadoran literature; metaliterature; Horacio Castellanos Moya; Cuaderno de Tokio